The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1007/s00253-013-4937-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Pseudoalteromonas sp. from fermented Korean food, as an antagonist to Vibrio harveyi

Abstract: The microbial intervention for sustainable management of aquaculture, especially use of probiotics, is one of the most popular and practical approaches towards controlling pathogens. Vibrio harveyi is a well-known pathogenic bacterium, which is associated to a huge economic loss in the aquaculture system by causing vibriosis. The present study is crafted for screening and characterization of anti-Vibrio strains, which were isolated from various traditional fermented Korean foods. A total of 196 strains have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…These qualities have allowed Pseudoalteromonas spp. to be used probiotically to prevent disease in cultured fish and shellfish (22)(23)(24)(25). Their beneficial effects are likely related, at least in part, to their secretion of inhibitors to competing microflora, including fish and shellfish pathogens.…”
mentioning
confidence: 99%
“…These qualities have allowed Pseudoalteromonas spp. to be used probiotically to prevent disease in cultured fish and shellfish (22)(23)(24)(25). Their beneficial effects are likely related, at least in part, to their secretion of inhibitors to competing microflora, including fish and shellfish pathogens.…”
mentioning
confidence: 99%
“…For example, probiotics isolated from the crab Scylla serrata used in the larviculture (100,000 liters) of the same crab improved larval survival by inhibiting bacteria of the family Flavobacteriaceae, which caused necrosis in larvae on day 7 of cultivation (Dan and Hamasaki, 2015). Similarly, Morya et al (2014) confirmed that the probiotic activity of the bacterium Pseudoalteromonas sp. in the aquaculture of the crab Portunus trituberculatus improved survival and reduced the pathogen load of Vibrio harveyi.…”
Section: Introductionmentioning
confidence: 79%
“…Zhou et al [30] Oth:Pseudoalteromonas sp. G-:V. harveryi ATCC 14126 [86] Where probiotics are divided as follows: lb: lactobacilli; bb: Bifidobacterium; oth: other; and pathogens are divided as follows: G+: Gram positive; G−: Gram negative; fng: fungi; prs: parasite; ins: insect. Table 4.…”
Section: Recent Results Of Determining the In Vivo Antimicrobial Assamentioning
confidence: 99%
“…Probiotic candidates have been accessed from very diverse habitats including faeces of breastfed human infants [65,69,80,85,95], faeces of healthy adults [9,15,65,70], faeces of elderly [81], faeces of children [25,96], breast milk [42], human saliva [52], vaginal isolates of healthy women [66,75], various fermented foods or beverages including raw or fermented milk [23,35,44], kefir [97], cheese [51,56,98], whey [99], yogurt [16,41], dahi [100,101], other dairy products [25,36,61], sourdough [102], sausages [17], fermented meat [24], kimchi [10,62], maize [25,59], fermented olives [103], Yerba mate [79], ragi [64], soy sauce [86], soil [104], as well as animal origin including rat faeces [71], geese [68], c...…”
Section: Discussionmentioning
confidence: 99%